The perceptions of nurses in a district health system in KwaZulu-Natal of their supervision, self-esteem and job satisfaction - L.R. Uys; A. Minnaar; S. Reid; J.R. Naidoo (AOSIS, 2004)
Supervision has been identified as a major issue in quality of care. Although increasing attention is being given to supervision in the District Health System, there have been no studies describing the current situation. This article describes a survey done in two health districts in KwaZulu-Natal involving 319 nurses from all types of government health care settings.